A study on serum potassium and serum magnesium levels in acute myocardial infarction with special emphasis on rhythm disturbance - K.I.S.N. VAISHNAVI; Vignesh C.; Mariraj I.; N. Krishna Geetha; Gowri Shankar A. (Romanian Medical Journal)
Background and objectives. Myocardial infarction (MI) is a severe cardiac event associated with plaque formation in arteries, leading to reduced blood flow to the heart. Arrhythmias, such as bradyarrhythmia or tachyarrhythmia, commonly accompany MI, contributing to its morbidity and mortality. Electrolyte disturbances, particularly potassium and magnesium imbalances, can exacerbate arrhythmic risks in MI patients. This study aimed to assess the incidence of alterations in serum potassium and magnesium levels during acute MI and their correlation with rhythm disturbances. Material and methods. A prospective analytical study was conducted with 150 patients diagnosed with acute MI based on ECG changes and elevated cardiac markers. Serum potassium and magnesium levels were measured, and rhythm disturbances were assessed using continuous cardiac monitoring and standard ECG. Spearman correlation analysis was performed to evaluate the association between serum potassium, serum magnesium, and rhythm changes. Results. The study investigated then demographic and clinical characteristics of participants and the potential relationship between serum electrolyte levels and arrhythmic changes. The mean age of the participants was 54.3 years, with a male predominance (76% male, 24% female). Among the participants, 50.67% had diabetes, 52% had hypertension, and 28% had both conditions. Serum electrolyte analysis showed elevated magnesium levels in 6.66% and elevated potassium levels in 12.66% of patients. Notably, arrhythmic changes in ECG were present in 62% of patients, with sinus tachycardia being the most prevalent (17%). However, statistical analysis revealed no significant correlation between serum magnesium, serum potassium, and rhythm changes (p >0.05). These findings suggest that while arrhythmic changes are common, they are not directly associated with elevated levels of these electrolytes, indicating the need for further investigation into other potential factors influencing arrhythmias in this population. Conclusion. Despite the prevalence of electrolyte disturbances in acute MI patients, this study found no significant association between serum magnesium, serum potassium levels, and rhythm disturbances. Further research is warranted to elucidate the complex interplay between electrolyte imbalances and arrhythmias in MI.